2020
DOI: 10.1155/2020/6723487
|View full text |Cite|
|
Sign up to set email alerts
|

Association between lncRNA GAS5, MEG3, and PCAT-1 Polymorphisms and Cancer Risk: A Meta-Analysis

Abstract: Purpose. Long noncoding RNAs (lncRNAs) have been widely studied, and single nucleotide polymorphisms (SNPs) in lncRNAs are considered to be genetic factors that influence cancer susceptibility. The lncRNA GAS5, MEG3, and PCAT-1 polymorphisms are shown to be possibly associated with cancer risk. The aim of this meta-analysis was to systematically evaluate this association. Methods. Studies were selected from PubMed, Web of Science, Embase, Google Scholar, Cochrane Library, the Chinese National Knowledge Infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The possible role of different genetic alterations in the development of gastric cancer has been studied [ 13 , 14 , 15 ]. Recent studies found that lncRNAs single-nucleotide polymorphisms (SNPs) may be involved in the carcinogenesis of gastric cancer [ 16 , 17 ]. An increasing amount of data demonstrate that gastric cancer patients have different lncRNA serum profiles compared with healthy controls [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The possible role of different genetic alterations in the development of gastric cancer has been studied [ 13 , 14 , 15 ]. Recent studies found that lncRNAs single-nucleotide polymorphisms (SNPs) may be involved in the carcinogenesis of gastric cancer [ 16 , 17 ]. An increasing amount of data demonstrate that gastric cancer patients have different lncRNA serum profiles compared with healthy controls [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although two studies have reported that the GAS5 ins/del polymorphism was associated with a predisposition to GC, the findings were not robust. 42,43 In the present study, we conducted meta-analyses, in addition to TSA analyses, FPRP tests, and single-tissue eQTLs. These results strongly demonstrated that GAS5 polymorphism rs145204276 is associated with the susceptibility to gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…52 The ANRIL locus is another example of a hotspot harboring more than 10 cancer risk SNPs, some of which are correlated with ANRIL expression. 53,54 Other lncRNAs linked to cancer SNPs include HOTAIR (HOX Transcript Antisense RNA), 55 HOTTIP (HOXA Distal Transcript Antisense RNA), 52 MALAT1 (Metastasis-Associated Lung Adenocarcinoma Transcript 1), 52 HULC (Highly Upregulated in Liver Cancer), 52 MEG3 (Maternally Expressed 3), 56 H19, 57 GAS5 (Growth Arrest-Specific 5), 56 and PTENP1 (Phosphatase And Tensin Homolog Pseudogene 1). 58 Mechanistic investigations of SNPs associated with ln-cRNAs have suggested that the risk variants may, in some cases, affect regulatory DNA sequences, thereby resulting in altered lncRNA expression.…”
Section: Lncrna Loci With Cancerassociated Snpsmentioning
confidence: 99%